Circumcised men’s perceptions, understanding and experiences of voluntary medical male circumcision in KwaZulu-Natal, South Africa - Celenkosini T. Nxumalo; Gugu G. Mchunu (South African Family Practice)
Background: KwaZulu-Natal, South Africa, has rolled out voluntary medical male circumcision (VMMC) in response to recommendations that regions with a high human immunodeficiency virus (HIV) prevalence adopt VMMC as an additional HIV prevention strategy. There is a paucity of South African data on the motivators, barriers and experiences of adult male candidates regarding VMMC. This study was conducted to analyse circumcised men’s perceptions, understanding and experiences of VMMC in KwaZulu-Natal, South Africa.